PENERAPAN MODEL PEMBELAJARAN BRAIN BASED LEARNING MENGGUNAKAN PEMBELAJARAN IPA TERPADU TIPE WEBBED DAN CONNECTED PADA MATERI PEMANASAN GLOBAL UNTUK MENINGKATKAN PENGUASAAN KONSEP DAN KPS - Yesi Nofla Meri; Ana Ratna Wulan (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2016)
Abstract The aims of the research are analyze the improvement of students’ concept mastery and science process skills through the implementation of Brain based Learning using integrated instruction of webbed and connected types on the topic of Global Warming. The method adopted was quasi experiment with the pretest-posttest control group design. The research instruments employed consisted of written tests of concept mastery and science process skills in the forms of multiple choice questions, observation sheets of the implementation of instruction for teachers and students, and response questionnaires for teachers and students. Research results show that there was not significant difference between the use of Brain based Learning model of connected compare to webbed types in improving students’ science process skills and concept mastery, with mean N-Gain scores for students’ both of them in the webbed-integrated and connected-integrated classes were both categorized as moderate. In addition, results of teachers’ and students’ response questionnaires reveal good responses to the learning model. Keywords: discovery learning; concept mastery; science process skills; shared-integrated; webbedintegrated Abstrak Tujuan penelitian ini adalah menganalisis peningkatan penguasaan konsep dan keterampilan proses sains (KPS) peserta didik melalui penerapan Brain based Learning dengan menggunakan pembelajaran terpadu tipe webbed dan connected pada materi Pemanasan Global. Menggunakan metode penelitian Quasi Experiment dengan desain Pretest-Posttest Control Group Design. Instrumen penelitian menggunakan tes penguasaan konsep dan tes KPS berbentuk tes tertulis jenis pilihan ganda, lembar observasi keterlaksanaan pembelajaran bagi guru dan peserta didik, serta angket tanggapan guru dan peserta didik. Hasil penelitian menunjukkan tidak terdapat perbedaan yang signifikan antara penerapan Brain based Learning tipe keterpaduan webbed dibandingkan dengan tipe keterpaduan connected untuk meningkatkan keterampilan proses sains peserta didik dan penguasaan konsep dimana rerata N-Gain baik untuk KPS maupun penguasaan konsep pada kelas keterpaduan connected dan kelas keterpaduan webbed berada pada kriteria sedang. Hasil angket tanggapan guru dan peserta didik memberikan tanggapan baik terhadap model pembelajaran. Kata Kunci: brain based learning; penguasaan konsep; keterampilan proses sains; keterpaduan connected; keterpaduan webbed Permalink/DOI: http://dx.doi.org/10.15408/es.v8i2.1811